Iron Age Terracotta Figurines from the Southern Levant in Context - Darby, Erin D.; Hulster, Izaak J. de (Culture and History of the Ancient Near East, 2021)
This interdisciplinary volume is a 'one-stop location' for the most up-to-date scholarship on Southern Levantine figurines in the Iron Age. The essays address terracotta figurines attested in the Southern Levant from the Iron Age through the Persian Period (1200-333 BCE). The volume deals with the iconography, typology, and find context of female, male, animal, and furniture figurines and discusses their production, appearance, and provenance, including their identification and religious functions. While giving priority to figurines originating from Phoenicia, Philistia, Jordan, and Israel/Palestine, the volume explores the influences of Egyptian, Anatolian, Mesopotamian, and Mediterranean (particularly Cypriot) iconography on Levantine pictorial material.